Pelatihan Penulisan Artikel untuk Publikasi E-Jurnal bagi Researcher Club - Gusneli Yanti; Zainuri Z; Shanti Wahyuni Megasari (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Journal is a place for publication of scientific works, the quality and content entirely lies in the written word. Plagiarism can be found because of negligence in writing the references. The purpose of this dedication is to help partners in understanding plagiarism, strategies to make articles using the application of Mendeley and scientific publications by organizing article writing training for members of the Research Club for publication. The method of implementation used was lectures and discussions. The training period lasts for 2 days, starting from the pre-test, material about journal publications, plagiarism, delays, and article writing strategies for e-journals and ending with post-test implementation. The pre-test results obtained an average value of 68,86 (adequate category), whereas for the assessment of the mastery of training material is 85,65 and the post-test is 86,62 both in the excellent category. From the average assessment, it can be proven that the article writing training for publication in e-journals for the Researcher Club is very useful and able to increase knowledge in writing articles for publication in e-journals for trainees.